The Effect of Processing on the Sodium, Potassium and Phosphorus Content of Six Locally Consumed Varieties of Manihot esculenta Grown in Bayelsa State - Tautua, Amos; Woriweinpre, Bamidele Martin; Madukosiri; Helen, Chinyelu (Pakistan Journal of Nutrition, 2009)
The minerals, sodium (Na), potassium (K) and phosphorus (P), content in the peels, raw unfermented pulp and fermented pulp of six local varieties of Manihot esculenta (cassava) grown and consumed in Bayelsa state were determined. The six varieties where identified as old cassava cultivars traditionally named Janet, Rowaina, Yomugha, Accra, Agric and Oguru in Bayelsa state. Flame photometer was used for the analysis of Na and K; while the colourimetric determination of P was done using vanado-molybdate method described in AOAC. The average mineral content determined (ppm) in the raw and fermented pulp from all the varieties were 6.33 and 3.33 for Na; 45.43 and 9.83 for K; 1.42 and 0.73 for P, respectively. The inner peels had more Na, K and P than the rest segments. Hence it appeared to be the mineral storehouse (probably due to pH values between 6.55 and 7.21) from where they are translocated to the pulp during growth. The outcome of processing by use of fermentation was a drastic reduction in the mineral content of fermented product. The effect of processing on the P content was deemed to be species-dependent. There was no detectable P in the fermented pulp of Accra variety.